2003
DOI: 10.1002/macp.200350070
|View full text |Cite
|
Sign up to set email alerts
|

Novel Semi‐Fluorinated Poly(ether imide)s Derived From 4‐(p‐Aminophenoxy)‐3‐trifluoromethyl‐4′‐aminobiphenyl

Abstract: An unsymmetrical diamine monomer 4‐(p‐aminophenoxy)‐3‐trifluoromethyl‐4′‐aminobiphenyl has been synthesized successfully. This monomer leads to the synthesis of different novel poly(ether imide)s when reacted with different dianhydrides like pyromellatic dianhydride (PMDA), benzophenone tetracarboxylic acid dianhydride (BTDA), 2,2‐bis(3,4‐dicarboxyphenyl) hexafluoropropane (6FDA), and oxy diphthalic anhydride (ODA). The poly(ether imide) prepared from this monomer on reaction with 6FDA is soluble in several or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 15 publications
3
32
0
Order By: Relevance
“…Kim's findings 29 insisted us to design the unsymmetrical monomer VI. However, the solubility of the poly(-ether imide)s derived from this monomer 30 was not on par with Kim's findings. This provoked us to further manipulate the chemical structures of the diamine monomer through simple chemistry that can result in useful polymer structures having the define set of properties.…”
Section: Introductionsupporting
confidence: 35%
See 1 more Smart Citation
“…Kim's findings 29 insisted us to design the unsymmetrical monomer VI. However, the solubility of the poly(-ether imide)s derived from this monomer 30 was not on par with Kim's findings. This provoked us to further manipulate the chemical structures of the diamine monomer through simple chemistry that can result in useful polymer structures having the define set of properties.…”
Section: Introductionsupporting
confidence: 35%
“…The synthesis of the compound 3-trifluoromethyl-4-fluoro-4 0 -nitro biphenyl was reported in our previous article. 30 Synthesis of diamine monomers VI, VII, and VIII…”
Section: Starting Materialsmentioning
confidence: 99%
“…All polymers are stable below 210°C, and the value of T g increases with decreasing n from T g = À3.5°C for n = 9 to T g = 148.5°C for n = 1. In general, low T g values suggest the polymer is soft while high T g values indicates rigid polymer structure [60,61]. We also found a reasonably good agreement between E app and T g as T g increases with increasing E app as shown in Fig.…”
Section: Thermal Properties Of Fc-containing Bulk Polymerssupporting
confidence: 65%
“…Recent studies demonstrated that polyimides derived from ether-bridged aromatic diamines with trifluoromethyl (-CF 3 ) groups are soluble high-temperature polymeric materials with low-moisture uptake, low dielectric constant, high optical transparency and low birefringence. [22][23][24][25][26][27][28][29] Imidazole ring is a useful n-type building block with high-electron affinity and good thermal stability and has been successfully incorporated in small molecules and polymers as the electron-transport component of OLEDs.…”
Section: Introductionmentioning
confidence: 99%